Combined Sleeve Gastrectomy and Omentoplasty Improves Inflammation and Insulin Resistance in Obese Rats with Type II Diabetes Mellitus: A Randomized Controlled Trials - Nugroho, Heri; Mughni, Abdul; Putranto, Indra Kusuma Adi; Prasetya, Anggoro Teguh; Novitasari, Vicky (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Diabetes mellitus (DM) is often associated with obesity, which can lead to chronic inflammation. Sleeve gastrectomy (SG) is a common treatment for obesity. Combining SG with omentoplasty, might help reducing inflammation in pancreatic beta cells. However, there is limited research regarding the combined effects of SG and omentoplasty in type 2 DM (T2DM). This study was conducted to fill this gap by evaluating the impact on body weight, insulin resistance, glucagon expression, and levels of interleukins (IL)-1, IL-6, and IL-10 in obese rats with type II DM.METHODS: An experimental study was conducted on 18 obese Wistar rats with DM that were randomized into: control, T1 (SG), and T2 (SG + omentoplasty). SG involved the surgical removal of a portion of the stomach to reduce its size, while omentoplasty utilized the omentum to target inflammation in pancreatic beta cells. Venous blood samples were taken from subjects one day before and ten days after the intervention to measure the biomedical parameters with various methods. Data was statistically analyzed using paired t-tests for pre-test and post-test differences, and Post Hoc tests or Mann-Whitney tests for hypothesis testing.RESULTS: All rats were confirmed to have obesity and DM according to the Lee index and blood glucose levels. T2 group exhibited a significant decrease in body weight, homeostatic model assessment of insulin resistance (HOMA-IR) values were lower, and glucagon expression, IL-1, IL-6, and IL-10 levels were significantly greater compared to both control and T1 groups.CONCLUSION: The combination of SG and omentoplasty significantly improves inflammation and insulin resistance in obese rats with T2DM.KEYWORDS: diabetes mellitus, sleeve gastrectomy, omentoplasty, inflammation, obesity